Effect of Integrated Use of Fertilizers, Farm Yard Manure, Green Manure and Zinc on Rice (Oryza sativa L.) Productivity and Soil Fertility - Ram Bharose; A. P. S. Dohare; Umesh Babu; Sanjeev Kumar; Ram Lakhan Pal (International Journal of Economic Plants)
The present investigation was conducted at the technology farmer field of district Shravasti during Kharif seasons 2021 and 2022. The Six treatment viz., control (T1), 100% RDF (T2), 50% RDF+Geen Manure (T3), 100% RDF +Zn (T4), FYM+Green Manure (T5), FYM+ Green Manure +Zn (T6) were replicated in randomized block design in Rice crop variety Rajendra Bhagwati. The data recorded revealed that 100% RDF +Zn increased Number of panicles hill-1, test weight, grain and straw yield. The treatment combination FYM+ Green Manure +Zn was found most effective improving yield and yield attributes. The maximum reduction of pH and maximum availability of O.C, N, P, K, S and zinc in soil was also recorded higher under FYM+ Green Manure +Zn. The nutrients status of soil was improved at higher level of nitrogen and the effect was more noticeable when nitrogen was applied by organic manure.